EFEKTIVITAS PENGGUNAAN LIMBAH PADAT AMPAS TAHU SEBAGAI PUPUK ORGANIK PADA PERTUMBUHAN DAN PRODUKSI TANAMAN BAYAM MERAH (Amaranthus tricolor L.) - Widya Lestari (UNIVERSITAS LABUHANBATU, 2019)
This research was conducted using randomized block design (RAK) with factorial one of three treatments: A0: 0 gr / polybag, A1: 100 gr / polybag, A2: 200 gr / polybag, A3: 300 gr / polybag, and continued with Duncan test. Parameters measured were plant height (cm), number of leaves (leaf), the heavy weight of the plant (gr). From these results we concluded as follows: In the observation of parameters with the highest dose of A3: 300 gr / polybag give real effect to the use of solid waste pulp out on plant height 14 HST and 21 HST, number of leaves at the end of the study, and the heavy weight of the plant Keywords: Tofu Dregs, Growth Red Spinach (Amaranthus tricolor L).